Implementasi Sistem Informasi Penjualan Solar Industri Berbasis Web dengan Metode Waterfall - Jourdan, Jourdan; Purwanto, Heru (Journal of Information System, Informatics and Computing, 2024)
PT Semesta Lautan Energi is a company that provides bunker service for industrial diesel fuel for shipping and non-shipping companies in Indonesia. The company still uses Microsoft Word and Excel applications in its business processes, which often leads to errors in making road letters, invoices and reports. The company also has difficulty in knowing the latest oil stock updates and details and takes a long time to get them because they have to match previous purchase and sales data. This research aims to create and implement a web-based industrial diesel sales information system to overcome problems in the current business process at PT Semesta Lautan Energi. the production of reports and invoices has been computerized so that it becomes more effective. The data search process also becomes faster and easier, and the company can manage data more efficiently. Data security is also improved with user roles to prevent data access by unauthorized parties